The book of Charlie : [large type] wisdom from the remarkable American life of a 109-year-old man - Von Drehle, David, 1961- (Center Point Large Print, 2023)
"When a veteran Washington journalist moved to Kansas, he met a new neighbor who was more than a century old. Little did he know that he was beginning a long friendship -- and a profound lesson in the meaning of life. Charlie White was no ordinary neighbor. Born before radio, Charlie lived long enough to use a smartphone. When a shocking tragedy interrupted his idyllic boyhood, Charlie mastered survival strategies that reflect thousands of years of human wisdom. Thus armored, Charlie's sense of adventure carried him on an epic journey across the continent, and later found him swinging across bandstands of the Jazz Age, racing aboard ambulances through Depression-era gangster wars, improvising techniques for early open-heart surgery, and cruising the Amazon as a guest of Peru's president. David Von Drehle came to understand that Charlie's resilience and willingness to grow made this remarkable neighbor a master in the art of thriving through times of dramatic change. As a gift to his children, he set out to tell Charlie's secrets. The Book of Charlie is a gospel of grit -- the inspiring story of one man's journey through a century of upheaval. The history that unfolds through Charlie's story reminds you that the United States has always been a divided nation, a questing nation, an inventive nation -- a nation of Charlies in the rollercoaster pursuit of a good and meaningful life."--